2007
DOI: 10.21829/azm.2007.231555
|View full text |Cite
|
Sign up to set email alerts
|

Pollen collection and honey bee forager distribution in cantaloupe

Abstract: Durante el verano del 2002 la colecta de polen y la distribución de las abejas (Apis mellifera L.) pecoreadoras fueron estudiadas en el cultivo de melón (Cucumis melo L., cv Cruiser ) bajo condiciones de riego por goteo y acolchado plástico. El lote experimental estuvo localizado cerca del Campo Experimental La Laguna del INIFAP, en el municipio de Matamoros, Coahuila, México. Dos experimentos se realizaron en el mismo predio, en lotes separados 800 m por una huerta de nogal. Ambas superficies de melón fueron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 25 publications
0
11
0
1
Order By: Relevance
“…However, in that case, the halictid bee did not visit female flowers as much as honeybee, resulting in a higher pollen deposition in the stigma by the latter species (Pisanty et al 2014). The main use of melon flowers as a nectar source by honeybee was also reported by Reyes-Carrillo et al (2007) in Mexico.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, in that case, the halictid bee did not visit female flowers as much as honeybee, resulting in a higher pollen deposition in the stigma by the latter species (Pisanty et al 2014). The main use of melon flowers as a nectar source by honeybee was also reported by Reyes-Carrillo et al (2007) in Mexico.…”
Section: Discussionmentioning
confidence: 91%
“…The main use of melon flowers as a nectar source by honeybee was also reported by Reyes‐Carrillo et al . () in Mexico.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the foraging activity fluctuates during the day from the morning until the evening. Reyes-Carrillo et al (2007) found high pollen collection in the early morning while low amounts of pollen were collected in the afternoon. Pernal and Currie (2010) reported a higher foraging rate mean during the afternoon period (36.02 foragers/min) than during the morning period (17.66 foragers/min).…”
Section: Foraging Timementioning
confidence: 86%
“…Colin et al (2004) developed a method to quantify the foraging activity of small colonies of honey bees confined in insect-proof tunnels using video recording. Pollen foraging activity can be monitored with pollen traps (Reyes-Carrillo et al 2007). In some studies, syrup foraging rate was investigated (e.g.…”
Section: Monitoring Of Foraging Activitymentioning
confidence: 99%
See 1 more Smart Citation